Modification of Waste Aggregate PET for Improving the Concrete Properties - Zoe Harmonie Lee; Suvash Chandra Paul; Sih Ying Kong; Susilawati Susilawati; Xu Yang (Advances in Civil Engineering)
Disposal of plastic wastes causes negative impacts including degradation of land and ocean and climate change. Reusing plastic wastes in concrete is one of the effective methods of reducing plastic disposal. Polyethylene terephthalate (PET) is one of the most abundantly available plastic wastes as it is commonly used for plastic bottles and food containers. This paper investigates the effects of treating PET wastes using hydrogen peroxide solution (H2O2) and calcium hypochlorite solution (Ca(ClO)2) before incorporating in concrete as coarse aggregate replacements. The physical and mechanical properties of concrete were analyzed for three different percentages, namely, 10%, 20%, and 30%, replacement of natural aggregates with plastic aggregates. For all percentage of replacements, it was found that chemically treated plastic aggregates have no effects on the fresh density, but the slump decreased due to roughened surface of treated plastic aggregates. Chemical treatment improved the bond strength between cementitious matrix and plastic aggregates and reduced the gap at the interfacial transition zone (ITZ). These phenomena contributed to the improvement the compressive strength and lower the permeability and porosity.